Maternal prenatal infection, early susceptibility to illness and adult psychotic experiences: A birth cohort study - Betts, K.; Williams, G.; Najman, J.; Scott, J.; Alati, Rosa (2014)
Background: Existing evidence has established that maternal infection during pregnancy and illness during early life are associated with later schizophrenia. No research has examined how the combination of these prenatal and postnatal exposures is linked to an increased risk to later schizophrenia and psychotic disorders. Methods: Participants from the Mater University Study of Pregnancy (MUSP), an Australian based, pre-birth cohort study were examined for lifetime DSM-IV positive psychotic experiences at 21. years by a semi-structured interview. Structural equation modelling was used to derive a general factor of psychotic experiences at age 21. Next, we undertook a number of separate analyses to investigate how prenatal infections and infant illness susceptibility are related to positive psychotic experiences in early adulthood, allowing for tests of moderation and mediation between the two risk factors. Results: After adjustment for important confounders, infant illness susceptibility was found to play a mediating role in the association between prenatal vaginal infection and later psychotic experiences. Whereby, infant illness susceptibility showed a direct association with psychotic experiences, while prenatal vaginal infection indirectly predicted psychotic experiences via infant illness susceptibility. Conclusion: Our findings suggest that illness susceptibility in early infancy may be central to the relationship between prenatal vaginal infection and later psychotic experiences. Further research is needed to establish the mechanisms that link these prenatal and postnatal exposures with psychotic illness in later life. © 2014 Elsevier B.V.